2020
DOI: 10.3390/ijms21082809
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Small Extracellular Vesicles Associated miRNAs in Periodontal Status—A Pilot Study

Abstract: This pilot study aims to investigate whether salivary small extracellular vesicle (sEV)-associated microRNAs could act as potential biomarkers for periodontal disease status. Twenty-nine participants (10 who were healthy, nine with gingivitis, 10 with stage III/IV periodontitis) were recruited and unstimulated whole saliva samples were collected. Salivary sEVs were isolated using the size-exclusion chromatography (SEC) method and characterised by morphology, EV-protein and size distribution using transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 44 publications
(58 reference statements)
1
83
0
Order By: Relevance
“…Another study compared saliva sEV isolation by UC and EQ and it showed that CD9 and CD81 expression was increased in EQ-sEV compared to UC-sEV [20]. Our very recent research demonstrated that SEC-sEV associated miRNAs (hsa-miR−140-5p, hsa-miR−146a−5p, and hsa-miR−628-5p) were only detected in sEV in periodontitis when compared to that of healthy controls [12].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Another study compared saliva sEV isolation by UC and EQ and it showed that CD9 and CD81 expression was increased in EQ-sEV compared to UC-sEV [20]. Our very recent research demonstrated that SEC-sEV associated miRNAs (hsa-miR−140-5p, hsa-miR−146a−5p, and hsa-miR−628-5p) were only detected in sEV in periodontitis when compared to that of healthy controls [12].…”
Section: Introductionmentioning
confidence: 83%
“…Commercially available SEC columns (miniPURE, HansaBioMed, Lonza) were used to fractionate the saliva sample according to the manufacturer's protocol (Figure 1b), as described previously [12]. Briefly, following 1:1 dilution with PBS, the samples were centrifuged at 300× g for 15 min, 1600× g for 15 min and 16,000× g for 20 min at 4 • C. The supernatant was loaded on an SEC column and 100 µL fractions were collected as indicated.…”
Section: Salivary Sev Isolation Using Sec Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact has popularized the use of SEC amongst its competitors for blood-based exosome-associated biomarker discovery research [52], [58]. SEC has been used successfully to isolate, purify and enrich exosomes from a variety of biological fluids including plasma [68]- [73], serum [74]- [76], bovine and human milk [77], [78], urine [79]- [82], saliva [83], [84], tears [83], cerebrospinal fluid [85], [86], synovial fluid [87], nasal lavage [89], seminal fluid [88] and stromal vascular fraction (SVF) from adipose tissue [63], [64] (Table 3). Recent findings reported at the ISEV Virtual Conference 2020 suggest SEC is superior to other techniques in isolation of pure exosomes from human body fluids (unpublished findings).…”
Section: Ideal Methods For Exosome Isolation: Secmentioning
confidence: 99%
“…In search for functional and regulatory periodontitis biomarkers small extracellular vesicles (sEV) in saliva related to miRNAs were recently investigated. One study reported that three miRNAs, hsa-miR-140-5p, hsa-miR-146a-5p and hsa-miR-628-5p in sEV, may have potential as diagnostic biomarkers for periodontitis (Han et al, 2020).…”
Section: Diagnostic Devices Salivary Proteome and Salivary Genomementioning
confidence: 99%